Investigasi pemanfaatan google classroom dalam pembelajaran matematika di madrasah: : a systematic literature review - Waritsman, Arsyil; Mulyana, Anna; Jumrana (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
The purpose of this article is to review, analyze and classify articles related to the use of google classroom in learning mathematics in madrasas. Furthermore, this article presents a systematic and comprehensive analysis of research related to the use of Google Classroom. The method used in this study is a systematic literature review in which the stages are the identification stage, the screening stage, the feasibility assessment stage and the inclusion stage. Of the 4920 articles searched through the Google Scholar database in the 2020-2022 range, only 11 articles met the requirements for further study and extracted the information contained in them. The results of the review found that (1) the use of Google classroom has been carried out in several provinces in Indonesia; (2) the implementation, development and effectiveness of using Google Classroom are quite diverse; (3) research approaches related to the use of google classroom include quantitative, qualitative, mixed methods and development; (4) the use of google classroom has a positive impact on students; (5) methods for evaluating the effectiveness of using Google Classroom can be done through pretest posttest, giving questionnaires and interviews; (6) Most of the topics discussed in mathematics are generally general, only a few discuss specific topics. In general, the results of this study are expected to encourage further research on the development of information technology services other than Google classroom related to their use in mathematics learning in madrasas, student learning experiences in participating in mathematics learning using google classroom, factors that contribute to student satisfaction when using google classroom services in learning mathematics and even the negative impacts and disadvantages of using google classroom in learning mathematics.